Post-mortem gross composition changes and differential weathering of immature and mature bone in an experimental burial environment. (August 2019) - Fisk, Shera; Berna, Francesco; Merrett, Deborah C.; Cardoso, Hugo F.V.
Abstract: In addition to differential culture-specific burial practices, the relative absence of juvenile skeletal remains in historic cemetery excavations has been explained by a comparatively rapid breakdown of immature bone. While the idea of differing breakdown rates between immature and mature bone is widely accepted, few experiments have provided evidence to support it. This study uses a porcine model to explore the role of bone maturity with regards to the overall susceptibility of the skeleton to physical and compositional degradation in an experimental buried environment. Samples ( n  = 104) were mechanically defleshed and left to degrade in a climate-controlled greenhouse environment, buried 10 cm below the soil surface. Every month, for the span of 12 months, 4 immature and 4 mature bones were collected. Weight loss on ignition analysis was performed to determine changes in the composition of bone, and bone weathering analysis was carried out to quantify the physical breakdown of bone. The results of this study indicate that in the first year after skeletonization of buried skeletal remains the compositional and physical breakdown of immature bones differ significantly from the changes seen in their mature bone counterparts. Immature bones seem more susceptible to compositional changes, but less affected by physical surface weathering. How these early differences in degradation affect the long-term survival of bone material and its post-depositional history in archaeological contexts, however, requires a longer study interval. Highlights: Immature and mature pig bones are used as a proxy for the human skeleton. A controlled burial environment allows for a direct comparison of breakdown. Immature bone undergoes more compositional change in the first year postmortem. Mature bone is more susceptible to physical weathering in the first year post-mortem.